2011
DOI: 10.1111/j.1440-1800.2011.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Relocating care: negotiating nursing skillmix in a mental health unit for older adults

Abstract: Mental health care in Australia in the last 20 years has moved from stand-alone psychiatric hospitals to general hospitals and the community. This paper reports an action research project exploring the experiences of nurses on an acute mental health unit for older adults staffed with a skillmix of mental health and general nurses, which recently transitioned from a psychiatric to a general hospital. The new service provides comprehensive health care, including the management of physical co-morbidity and a reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…These results showed that despite Chinese psychiatric inpatients being relatively passive, they still rated collaboration with healthcare professionals in deriving their treatment and care plan as important. The results of the current study were in line with other studies on non-Chinese populations that psychiatric inpatients do consider that their participation in their treatment plan as important [ 32 , 34 36 ]. In a study conducted in America on shared decision-making preferences of patients with severe mental illness, most of the patients preferred shared decision making, particularly in relation to their mental health care [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…These results showed that despite Chinese psychiatric inpatients being relatively passive, they still rated collaboration with healthcare professionals in deriving their treatment and care plan as important. The results of the current study were in line with other studies on non-Chinese populations that psychiatric inpatients do consider that their participation in their treatment plan as important [ 32 , 34 36 ]. In a study conducted in America on shared decision-making preferences of patients with severe mental illness, most of the patients preferred shared decision making, particularly in relation to their mental health care [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…As regards research, multimorbidity has mainly been addressed in studies in the medical domain, although the broader health science orientation has recently addressed topics also relevant from the perspectives of organization and management sciences (see also the library of International Research Community on Multimorbidity, 2013). In addition to the research on patient perspectives described above, these studies include such issues as health system design (Boyd andFortin, 2010), integration (de Bruin et al, 2012;Sampalli et al, 2012), coordination and quality of care (Burgers et al, 2010), competencies (Henderson et al, 2011) and costs of care (Glynn et al, 2011;Lehnert et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Henderson et al. ), analyses that also consider the intersections of gender and racialized power relations within this setting are less visible in the literature. What our analysis adds is how the neoliberal‐inspired changes to the organization and conditions of work intersect and buttress racialized and gendered structures and assumptions to further devalue nurses and their care work.…”
Section: Discussionmentioning
confidence: 99%
“…The mental health sector has been linked to this market‐based reform direction with its attendant intensification of work and multiskilling of care (Henderson et al. ).…”
mentioning
confidence: 99%